PERUSAKAN LINGKUNGAN DAN PENCEGAHAN KEJAHATAN - Kusumawardhani, D.T.P. (Jurnal Legislasi Indonesia, 2009)
Refering to the numbers of contamination and/or environmentharm cases, or can be also conceived of environmental crime,both for happened in our society and around the world, thenshow that environment that properly made everlasting exactlydisregarded. If this condition will be long drawn out, then, it canbe imagined that the environment where we properly can live insecure and prosperous, healthy and humanize will not beoccured. This Article is strived to discuss an existance of theefforts of environment crime prevention that it is of course have ascope, problem, special method attention and at the same timeis its challenge arena for its development. This Paper is a briefexploration that stemed from library study and still as an earlyunderstanding for the implemaentation of the environment crimeprevention strategy. The writer believe that is not easy to get adeliberation about the environment crime prevention strategywhich efficient through the relative shorten. Nevertheless,hopefully this article can introduce some initial ideas which isprobably to be expostulated and completed furthermore.